2004
DOI: 10.4049/jimmunol.173.5.3392
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-10 Induction from Dendritic Cells in Response to Mycobacterium tuberculosis Is Predominantly Dependent on TLR2-Mediated Recognition

Abstract: The initial TLR-mediated interaction between Mycobacterium tuberculosis and dendritic cells is critical, since the cytokine production that ensues can greatly influence the class of adaptive immunity that is generated to the pathogen. In this study, we therefore determined the dependency on TLR2 and TLR4 for M. tuberculosis-induced cytokine production by murine dendritic cells. A key new finding of this study is that production of IL-6 and IL-10 from dendritic cells in response to M. tuberculosis is principall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
89
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 45 publications
6
89
0
4
Order By: Relevance
“…Similar to observations in the study by Weiss et al (2007) no differential transcription of IL10 was observed. Our finding of relative upregulation of IL6 is in agreement with studies in TLR2À/À mice suggesting a role of TLR2 in immunosuppression during mycobacterial infection via upregulation of IL6 (Jang et al, 2004), which may also play a role in cattle.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to observations in the study by Weiss et al (2007) no differential transcription of IL10 was observed. Our finding of relative upregulation of IL6 is in agreement with studies in TLR2À/À mice suggesting a role of TLR2 in immunosuppression during mycobacterial infection via upregulation of IL6 (Jang et al, 2004), which may also play a role in cattle.…”
Section: Discussionsupporting
confidence: 91%
“…In light of these in vitro findings, we speculate that the preferential signaling via TLR2 in active TB results in a net anti-inflammatory effect that functionally deactivates macrophages harboring M. tuberculosis and thus allows unrestricted proliferation and overt disease. The notion that M. tuberculosis-mediated TLR2 signaling is anti-inflammatory was previously posited by Salgame et al (73,75). The consequence of heightened expression of SOCS1, IRAK-M, and TLR2 as well as potent soluble suppressors of macrophage activation such as IL-10 and TGF-␤ may result in lower antimicrobicidal activity, as shown by Ͻ30% of alveolar macrophages expressing NOS2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased TLR2 expression may provide M. tuberculosis another avenue to exploit immune subversion, because many M. tuberculosis ligands detected by innate immune cells are apparently sensed by TLR2. These include lipoproteins and the ESAT-6 protein, each of which has been shown to impair immune activation and/or favor the production of more antiinflammatory than inflammatory cytokines (36,(71)(72)(73). Through a systematic comparison of innate immune responses after cell stimulation with agonists specific for TLR2, TLR3, TLR4, TLR5 and TLR7, Re and Strominger found that TLR2 stimulation led to the blockage of subsequent cell activation by TLR3 and TLR4 agonists (74).…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 induces IL10 production and is linked to IL10-mediated immune suppression. [43][44][45] Furthermore, TLR2-dependent signals were recently shown to mediate the generation of downmodulating T-regulatory cells, IL10-secreting immune cells with important function in balancing immune response. 46,44 We hypothesize that under the circumstance of 'enhanced' IL10 sensitivity owing to the IL10RA AAgenotype, the production of TNF-a and further proinflammatory cytokines is decreased, with negative consequences on cellular immunity.…”
Section: Discussionmentioning
confidence: 99%